Grip strength after forearm cooling in healthy subjects - Pedro Henrique Reis Rabelo; Kárenn Klycia Pereira Botelho; Franassis Barbosa de Oliveira
Abstract Introduction: Muscle strength has shown different responses to the cooling of neuromuscular tissue and its behavior is still unclear. Objective: To verify the behavior of maximum grip strength before and after forearm cooling. Methods: The cooling intervention consisted of immersing the forearm up to the elbow in water cooled to 10° C. Grip strength was assessed using a dynamometer prior to cooling, immediately after immersion, and at 5, 10 and 30 minutes of forearm exposure to ambient temperature (recovery phase) concomitantly to measurement of skin surface temperature. The sample consisted of 30 healthy individuals. Results: Grip strength decreased significantly (p < 0.05) between the period prior to cooling and all the time intervals following immersion in ice water. There was also a gradual increase in grip strength during the recovery phase, with significant differences (p < 0.05) between the mean immediately after immersion and means at 5, 15 and 30 minutes after exposure to ambient temperature. Conclusion: The results indicate that immersion in ice water (10ºC) for 15 minutes significantly reduced (p < 0.05) grip strength for up to 30 minutes after forearm cooling. Strength also recovered progressively after removal of the cold stimulus. Further research is needed to obtain definitive results regarding the effects of cooling on muscle strength in healthy individuals.